The Importance of Full and Frank Disclosure in Family Law Financial Proceedings and the Many Consequences of Non-Disclosure. (2017) - Kopsen, Hugh P K; Carroll, Robyn
This article examines the duty of full and frank disclosure of parties to family law financial proceedings in Australia, and the potential consequences of failure to comply with this fundamental obligation. The duty is briefly compared and contrasted with disclosure requirements in civil litigation and criminal proceedings to demonstrate the uniqueness of the family law position. The rationale and content of the duty is considered in light of recent cases including the High Court decisions of Stanford v Stanford (2012) 247 CLR 108 and Hall v Hall (2016) 257 CLR 490. The article presents a three-pronged taxonomy of the consequences of non-compliance with the duty, namely evidential, procedural, and final orders/related consequences. We conclude that the absolute nature of the duty and the comprehensive nature of the potential consequences of failure to make full disclosure mean that parties and legal practitioners do so at their peril.